Makala ya simulizi ya ugonjwa wa fungashada ya migomba-Tanzania - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
The documentary on BBTV (banana bunchy top virus) explores its intense impacts in affected region(s) of Tanzania, highlighting its effects on banana crops, agricultural and livelihoods. It searches into efforts to mitigate its spread, the challenges faced by farmers, and strategies for resilience in the face of this inversive agricultural threat.